Electric conductivity of the exudate of beans from diferents coffee genotipes (Caffea arabi L.) - Prete, Cássio Egidio Cavenaghi; Abrahão, Jairo Teixeira Mendes (Semina: Ciências Agrárias, 2004)
1 PROBLEMA<!–[if gte mso 9]> Papelaria Dinossauro 10.2625 <![endif]–><!–[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-alt:Verdana; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> In order to study the influence of genotype on coffee electrical conductivity, an experiment was conducted at Escola Superior de Agricultura Luiz de Queiroz Agricultural Department with materials from Agronomic Institut of Campinas. Eleven cultivars were tested. An inverse relation between electrical conductivity and beverage quality was found. Cultivars were ranked in a increasing order of quality: Icatu Vermelho Acaia, Caturra Vermelho, Icatu Amarelo, Novo Mundo, Catuai Vermelho, Catuai Amarelo, Bourbon Vermelho, Caturra Amarelo, Bourbon Amarelo e Arabica.